A Study on Customer Perception towards Purchase Intention of Electric Cars in Bandar Lampung - Mujuni Kenneth Nyakairu; Viola De Yusa (Proceeding International Conference on Information Technology and Business, 2022)
Electric vehicles (EVs) are one of a prominent solution for the sustainability issues needing dire attention like global warming, depleting fossil fuel reserves, and greenhouse gas (GHG) Emissions. Conversely, EVs are shown to emit higher emissions (measured from source to tailpipe) for the fossil fuel-based countries, which necessitates renewable energy sources (RES) for maximizing EV benefits. EVs can also act as a storage system, to mitigate the challenges associated with RES and to provide the grid with ancillary services, such as voltage regulation, frequency regulation, spinning reserve,Despite the fact that quick progress of worldwide economy and new edge technology advanced human civilization, it has also prompted the notable harm to the ecological surroundings. So, now the time has come to think seriously to save the environment and sustainable development. The new energy vehicles (electric vehicles) are one of the solutions. This paper focuses on the customer perception towards purchase intention of consumer, their interest and other influencing factors towards electric cars by analyzing the variables that impact individual expectations for adopting Electric Cars. What makes consumers adopt energy-sustainable innovations? Drawing from psychological research on environmental behaviors, we propose a model integrating attitudinal factors, normative factors and self-control to explain the purchase of electric vehicle This study offers insights into the development of marketing program for EV in bandar Lampung the findings will help EV manufacturers to facilitate EV purchases. Keywords-Customer perception, Purchase intention, Electronic cars